THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF PASER DISTRICT - Dedy Darmawan; Achmad Appriannor Firdaus; Muhammad Akbar; Muhammad Dirvansyah; Harmayanto Harmayanto (Jurnal Mahasiswa Manajemen, 2025)
The purpose of this study is to examine the influence of organizational culture consisting of seven dimensions, namely innovation and risk-taking (X1), attention to detail (X2), result orientation (X3), people orientation (X4), team orientation (X5), aggressiveness (X6), and stability (X7), both simultaneously and partially, on employee performance at the Department of Population and Civil Registration of Paser Regency (Y). This study employed a saturated sampling technique with a total of 67 employees as respondents. The research instrument in the form of a questionnaire was first tested for validity and reliability, and the results showed that 18 statements were valid (r-calculated > r-table) and reliable (Cronbach’s Alpha 0.967 > 0.60). The multiple linear regression analysis produced the equation Y = -1.039 + 0.137X1 + 0.142X2 + 0.176X3 + 0.170X4 + 0.223X5 + 0.170X6 + 0.198X7. The multiple correlation coefficient of 0.951 indicates a very strong relationship between organizational culture and employee performance, while the Adjusted R² value of 0.893 shows that the independent variables explained 89.3% of the variation in employee performance. The simultaneous test confirmed that organizational culture as a whole significantly affects employee performance (F-calculated 80.055 > F-table 2.17; sig. 0.000 < 0.05). The partial test results demonstrated that all dimensions of organizational culture significantly influence employee performance, with t-calculated values greater than t-table (2.001). The most dominant dimension is team orientation (X5), with the highest t-calculated value of 3.241 and a significance level of 0.002. Therefore, the hypothesis stating that innovation and risk-taking (X1) is the dominant factor was not supported; instead, team orientation (X5) was found to have the strongest effect on employee performance.